Outcome of Primary Ankle Fusion with Modified Blair Technique in Hawkins Type III Fracture of the Talus - Thapa, Santosh; Rajthala, Ashish; Shrestha, Oshan; Kumar Jha, Ranjib; Dhoj Kunwar, Suman (Nepal Orthopaedic Association Journal, 2024)
Introduction: The rates of post-traumatic osteoarthritis after Talar neck and body fractures vary between 16% and 100%, as the Talar body gets most of its blood supply in a retrograde manner from the anastomosis, this predisposes it to develop avascular necrosis. The need for secondary arthrodesis to address pain, discomfort, malunion, and non-union increases to 40%. Due to such high rates of secondary arthrodesis, the concept of primary arthrodesis for high-grade complex fractures is emerging.Methods: This retrospective study was conducted in a tertiary-level hospital among patients with talus fractures who had undergone Modified Blair fusion in the institution. Data from January 1, 2017, to December 30, 2022, was accessed for patient selection. A median with an interquartile range was used for continuous variables. Data analysis was performed in SPSS 20.Results: Nine patients were included in this study, with a male-to-female ratio of 8:1, an age of 37 (29 51), and an average follow-up of 18 (14–26) months. All fusions were united without the need for secondary operations in 19 (16–20.5) weeks. The AOFAS at 12 months was 74 (63–81). There were two excellent results (tibiopedal motion of 15°–20°), five good results (tibiopedal motion of 10°–15°), and two poor results (tibiopedal motion of less than 10°).Conclusion: Modified Blair Fusion is an effective modality with a minimal complication rate and can be performed as primary surgery for Hawkins type III Talar neck body fractures.